Sex Selection of Mice Embryo by Ericsson Method Using Intra-Peritoneal Insemination - Hadi, Ilaf Hassan (The Iraqi Journal of Veterinary Medicine, 2012)
The objective of the study was to investigate the effect of Ericsson Albumin Method to separate Y- from X-bearing sperms in mice. The sperms were obtained from caudal epididymis of male mice and prepared by Ericsson method using albumin in two concentrations (8% and 18%) fallowed by intra-peritoneal insemination of female mice. The study showed there was a significant increase (P>0.05) in pregnancy rate in female mice that inseminated by sperms were prepared by Ericsson method. Also, the results demonstrated that Ericsson method was found (75%) effective for male gender selection compared to conventional method (51.25%) without separation of Y- from X-bearing sperms.